Topics on Critical Issues in Neonatal Care - Mauricio Barría, R. (IntechOpen, 2022)
Neonatology is one of the areas of greatest development and evolution within pediatrics. Every year there are advances in the management of the different diseases that newborns develop, which makes it necessary to refresh knowledge on traditional and other emerging issues. This book includes six chapters that address critical and relevant issues in neonatal care and seeks to contribute to the clinical work of health teams in neonatal units.